New fossil giant lacewings from the Middle Jurassic Jiulongshan Formation of China (Neuroptera, Ithonidae) - Xu, Yifan; Zheng, Bingyu; Fang, Hui; Shih, Chungkun; Ren, Dong; Wang, Yongjie (Zootaxa, 2021)
A new genus with a new species, Fuscopolystoechotes reticulatus Xu, Zheng, Shih & Wang, gen. et sp. nov., and a new species Lichenipolystoechotes fenestratus Xu, Fang, Shih & Wang, sp. nov. of Ithonidae, are described from the Middle Jurassic Jiulongshan Formation, Inner Mongolia, China. Both new species are assigned to Polystoechotes genus-group mainly based on the combination of following characters: the distinctly narrowed costal space in distal half, presence of recurrent humeral veinlet and ScA, absence of interlinked crossveins in between costal crossveins, converged ScP and RA and pectinately branched MA and MP in distal. But the new genus of Fuscopolystoechotes gen. nov. is differentiated from all other genera by a combination of characters, i.e., specialized markings on forewing; scp-ra crossveins absent; CuP with pectinate branches and crossveins in RP–A area complicated. These two new species with the remarkable markings in forewings are considered to be adapted for the particular Mesozoic environments for camouflage or mimicry.